2023
DOI: 10.1513/annalsats.202208-720oc
|View full text |Cite
|
Sign up to set email alerts
|

Higher- versus Lower-Dose Corticosteroids for Severe to Critical COVID-19: A Systematic Review and Dose–Response Meta-analysis

Abstract: RationaleCorticosteroids are standard of care for patients with severe COVID-19. However, the optimal dose is uncertain. ObjectiveTo compare higher doses of corticosteroids with lower doses in patients with COVID-19. MethodsWe searched MEDLINE, Embase, Cochrane Central Register of Controlled Trials, MedRxiv, and Web of Science from inception to August 1 st , 2022, for trials that randomized patients with severe-to-critical COVID-19 to corticosteroids, standard care, or placebo. Reviewers, working in duplicate,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, a meta-analysis that included 20 studies of 10 155 patients with severe or critical COVID pneumonia (defined as tachypnea >30/min, oxygen saturation <90% on room air, or ARDS) concluded that dexamethasone 12 mg daily for 10 days was associated with reduced mortality compared with 6 mg daily for 10 days (absolute risk difference, −14 per 1000; 95% CI, −26 to −2) . Therefore, according to this study, patients requiring supplemental oxygen at greater than or equal to 10 L/min, noninvasive ventilation, or invasive mechanical ventilation may benefit from treatment with higher-dose dexamethasone…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis that included 20 studies of 10 155 patients with severe or critical COVID pneumonia (defined as tachypnea >30/min, oxygen saturation <90% on room air, or ARDS) concluded that dexamethasone 12 mg daily for 10 days was associated with reduced mortality compared with 6 mg daily for 10 days (absolute risk difference, −14 per 1000; 95% CI, −26 to −2) . Therefore, according to this study, patients requiring supplemental oxygen at greater than or equal to 10 L/min, noninvasive ventilation, or invasive mechanical ventilation may benefit from treatment with higher-dose dexamethasone…”
Section: Discussionmentioning
confidence: 99%
“…Higher versus lower doses of corticosteroids in hospitalised adults with COVID‐19 have also been compared in other systematic reviews and meta‐analyses of observational studies and RCTs 14–17 . All used a higher cut‐off for high‐dose treatment (range 10–20 mg of dexamethasone) than in our review 14–17 . None assessed days alive without life support, which may be of importance during periods with high caseloads and strained ICU capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In one systematic review of both observational studies and RCTs comparing different doses of corticosteroids, several RCTs 18,20,28 included in our systematic review were not eligible as high‐dose treatment was defined as >100 mg methylprednisolone or >20 mg dexamethasone daily 14 . Pitre et al 15 included 20 RCTs assessing corticosteroids versus placebo or no treatment or different doses of corticosteroids in patients with severe or critical COVID‐19 and found that higher doses probably reduced mortality (moderate certainty of evidence). This review only included seven out of the 17 RCTs in our review, which may explain the observed difference 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations